Introduction to the 5 Pillars of Community-Based Total Sanitation (STBM) Education at Indonesian Schools in Singapore (SIS) - Ayu Safira; Afri Ahya Suardi; Rose Fatmadewi; Rama Arianto Widagdo; Siti Nur Azizah (Journal of Society, Community and Business Development, 2025)
This community service activity was carried out to provide education about the 5 Pillars of Community-Based Total Sanitation (STBM) at Sekolah Indonesia Singapore (SIS). The STBM program is an approach to change hygienic and sanitary behavior through community empowerment, which has five main pillars: (1) Stop Open Defecation, (2) Hand Washing with Soap, (3) Drinking Water and Household Food Management, (4) Household Waste Management, and (5) Household Liquid Waste Management. This program aims to improve public health and prevent environment-based diseases. The service method used is Community Development, with the main activities in socialization, counseling, and evaluating grade 3 and 4 students at SIS. The results of this activity show an increase in students' knowledge, attitudes, and behaviors towards healthy sanitation. Before counseling, most students only understood the importance of washing hands, but after education, they have understood all five pillars of STBM. With the interactive delivery method using posters, students become more enthusiastic and show positive changes in a clean and healthy lifestyle. This activity has successfully achieved its goals and is expected to create a generation that is more concerned about environmental cleanliness and sanitation.